the Concept of the Street Vendors’ Management in the Border Area - Veneranda Rini Hapsari; Benedhikta Kikky Vuspitasari; Deffrinica Deffrinica (STKIP Singkawang, 2019)
This study aims to determine how the concept of street vendors in Bengkayang Regency, so as to improve the image of the region. The research method uses descriptive qualitative methods. Research location in Bengkayang Regency. The object of this study is the street vendors, which is one of the jobs using the roadside area to sell, as well as the street vendors in Bengkayang Regency. Initially, the street vendors sell at night in the terminal area, but because the terminal will build a shop, the street vendors moved to the Dekranasda area. In these areas it was felt rather quiet of the buyer, so the street vendors moved to sell at the edge of the roadside shophouse that was closed. Thus actually disturbing the view of Bengkayang Regency city planning. But it cannot blame these street vendors either, because it is their livelihood and indirectly adds to regional income. The results of this study are a form of business facilities that harmonious and memorable transparent street vendors so as not to interfere with the visual aesthetics of the corridors on the road, so as to make the road neat and attractive.